Anti‐migration performance of EPDM composite improved by octadecylamine‐functionalized graphene oxide. Issue 31 (3rd June 2022) - Lu, Zhehong; Hu, Yubing; Zhang, Bohan; Zhang, Guangpu; Guo, Fan; Jiang, Wei
Abstract: In this paper, the ethylene propylene diene monomer (EPDM) was used as a composite matrix and octadecylamine‐functionalized graphene oxide (GA) was applied as insulation nanofiller to prevent plasticizer migration. To study the anti‐migration behavior of EPDM under plasticizer environment and different temperatures, we investigated the diffusion of dioctyl phthalate (DOP) in EPDM and its composites. The migration kinetics of DOP into EPDM composites with respect to filler and temperature were observed by the immersion absorption method. The process is dynamic and conforms to Fick's law. The composite show a 90% increase in tensile strength and 151% improvement in elongation at break by the addition of 5 phr filler of GA. Meanwhile, the EPDM/GA composite show an obviously improved anti‐migration performance, compared to pure EPDM at different temperatures, the composite show a 22.68%, 17.35%, 14.95%, 7.63% increase. Well layer‐structure of graphene offers a chance to improve the anti‐migration performance of insulation. Abstract : The EPDM/GA composite show an outstanding anti‐migration performance.